Nepal “Ask me anything” Session: Responses to audience questions - Kaye, Tom; Groeneveld, Caspar; Moss, Caitlin; Haßler, Björn (EdTech Hub, 2020)
On Thursday, 30 April 2020, the EdTech Hub participated in an “Ask me anything” session for policy-makers and funders in Nepal. The session focused on designing high-quality, effective, distance education programmes during the COVID-19 pandemic. Participants included high-level officials from the Nepalese government (e.g., the Ministry of Education, Science and Technology, the Curriculum Development Office and the Education Review Office), representatives from development partners (e.g., the World Bank, UNICEF and USAID) and other education organisations (e.g., OLE Nepal). The session was convened for two purposes. First, to consider international good practice and current trends in distance education during the COVID-19 pandemic, presented by the World Bank EduTech team and the EdTech Hub. Second, for the EdTech Hub team to gather questions from participants, to be able to target guidance specifically to the situation in Nepal. This document provides answers to a consolidated list of 10 questions received from stakeholders during the session. To consolidate any overlap, we have occasionally combined multiple questions into one. In other cases, where multiple important issues required a focused response, we split apart questions.
Keywords: Author:Haßler; Author:OpenDevEd; Björn-CV-OECS; C:Nepal; F: Helpdesk response; LP: English; _C:Austria AUT; _C:Bangladesh BGD; _C:Kenya KEN; _C:Korea XKOR; _C:Liberia LBR; _C:Nepal NPL; _C:Pakistan PAK; _C:Singapore SGP; _EdTechHub_Output; __C:filed:1; __C:scheme:1; _cover:v1; _r:ImportedToMyEducationEvidence; _zenodoETH; docs.opendeved.net; dode_eth-src-dode; dode_eth-trf2-dode